2022
DOI: 10.3390/plants11060809
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Diversity of Flavan-3-Ols in Grape Seeds: Modulating Factors and Quality Requirements

Abstract: Grape seeds are a rich source of flavan-3-ol monomers, oligomers, and polymers. The diverse profile of compounds includes mainly B-type procyanidins (especially C4→C8 linked molecules) and the key monomers, catechin, and epicatechin that are positively implicated in the ‘French Paradox’. Today grape seed nutraceuticals have become a multi-million-dollar industry. This has created incentives to elucidate the variations in chemistry across cultivars, to identify signs of adulteration, and to understand the intri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 124 publications
0
15
0
Order By: Relevance
“…These compounds play an important role in the quality and characteristics of wine and also have the function of a natural preservative. The flavan-3-ols of grape seeds possess various biological effects on human health and contribute to the health properties of wine [ 55 ]. Figure 7 a–d show the dimensionless content of flavan-3-ols (epicatechin gallate, galocatechin gallate) in GP extracts before biological treatment (‘0’ day) and after 1–15 days of biological treatment with eleven filamentous fungi (TV6, TV8, TV AG613, GL, GR, RO, PC, CS, PE, HG and TG).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These compounds play an important role in the quality and characteristics of wine and also have the function of a natural preservative. The flavan-3-ols of grape seeds possess various biological effects on human health and contribute to the health properties of wine [ 55 ]. Figure 7 a–d show the dimensionless content of flavan-3-ols (epicatechin gallate, galocatechin gallate) in GP extracts before biological treatment (‘0’ day) and after 1–15 days of biological treatment with eleven filamentous fungi (TV6, TV8, TV AG613, GL, GR, RO, PC, CS, PE, HG and TG).…”
Section: Resultsmentioning
confidence: 99%
“…Procyanidins are formed by oxidative condensation of (+)-catechin and/or (−)-epicatechin units. Consistently the most abundant procyanidin dimer in grape seeds is procyanidin B2 [ 55 ]. Procyanidins are characterized by antioxidant activity and the ability to specifically bind proteins and regulate cellular signaling pathways.…”
Section: Resultsmentioning
confidence: 99%
“…This difference might be due to the accumulation pattern of flavan-3-ols. Studies have shown that the accumulation pattern of flavan-3-ols in grape berries exhibited a trend of increasing and then decreasing ( Padilla-González et al, 2022 ), generally reaching the highest concentration at the véraison stage, and then showing a decreasing trend, but the synthesis of anthocyanin showed a rapid accumulation process during the véraison stage. In combination with the phenological period, vintages with insufficient light often have more rainfall during the véraison stage, and rainfall slows down the accumulation of anthocyanin and flavonol, while the decomposition rate of flavan-3-ol decreases, which in turn causes the phenomenon of low anthocyanins and flavonols concentrations and high flavan-3-ols concentrations in berries at maturity in vintages with insufficient light and more rainfall ( Blancquaert et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Results obtained for total flavan-3-ol content, as the phenol group most-specific to grape seeds, also differed from variety to variety. As reported before, flavan-3-ol diversity in grape seeds is primarily influenced by species, variety and environment [ 51 ]. Finally, even though higher values were observed for EtOH extracts, statistical significance was not reached ( p = 0.1892).…”
Section: Resultsmentioning
confidence: 94%